The Impact of Using Virtual Reality on Writing Descriptive Text: An Experimental Study at Junior High School - Qurrotul A’yun, Fika (JEET, Journal of English Education and Technology, 2024)
The purpose of this study is: (1) To find out the impact of Virtual Reality on writing descriptive text in 7th grade at SMP YPI Darussalam 1 Cerme. In this study, researchers used a quantitative method approach with a type of Pre-Experimental research with the design of One Group Pretest Posttest. The result shows that the difference in the writing descriptive text between the student taught using Virtual Reality (VR) medium and those taught not using Virtual Reality (VR) medium is significant. By comparing the magnitude of the “t” obtained in observational calculations (to=5.71)and the size“t” listed in the value table t (tt.ts. 5% = 2.04 and tt.ts.1% = 2.76). Then it can be known that the to is greater than the tt: 2,04<5,71>2,76. Because the to is bigger than tt, then the Ho filed were rejected, and Ha is accepted. This suggests that there was an impact on the use of VirtualReality medium on a descriptive text writing of the 7C class at SMP YPI Darussalam 1 Cerme. From the explanation above, the implementation of Virtual Reality (VR) medium in teaching and learning process gives a positive effect on the students. Because they can study easily and more fun without any burden It can be done because by fun learning, knowledge and sharing can be maintained well